Variable phenotypes are associated with PMP22 missense mutations. - Russo, M; Laurá, M; Polke, J; Davis, M; Blake, J; Brandner, S; Hughes, R; Houlden, H; Bennett, D; Lunn, M; Reilly, M (2011)
Charcot-Marie-Tooth disease (CMT) is the commonest hereditary neuropathy encompassing a large group of clinically and genetically heterogeneous disorders. The commonest form of CMT, CMT1A, is usually caused by a 1.4 megabase duplication of chromosome 17 containing the PMP22 gene. Mutations of PMP22 are a less common cause of CMT. We describe clinical, electrophysiological and molecular findings of 10 patients carrying PMP22 missense mutations. The phenotype varied from mild hereditary neuropathy with liability to pressure palsies (HNPP) to severe CMT1. We identified six different point mutations, including two novel mutations. Three families were also found to harbour a Thr118Met mutation. Although PMP22 point mutations are not common, our findings highlight the importance of sequencing the PMP22 gene in patients with variable CMT phenotypes and also confirm that the PMP22 Thr118Met mutation is associated with a neuropathy albeit with reduced penetrance.